PENERAPAN STRATEGI RECIPROCAL TEACHING MENGGUNAKAN MICROSOFT POWER POINT DALAM PEMBELAJARAN MATEMATIKA - Berlian Putri S (Universitas PGRI Adi Buana Surabaya, 2015)
One of the problems in the mathematical learning in junior high was the low ability students in solving math problems that are packed in the form of a question which more emphasis on understanding and mastery of a particular subject matter. Addressing such matters, the solution can be used i.e. through Reciprocal Teaching approach, in order to improve understanding about the concept of students Determines the slope of the equation of a straight line, engaging students actively in the learning, and encourages independent learning-centered students so teachers only as a facilitator.The methods used in this research is a method of tests given to students in order to know student complete learning. And given the now after learning method to determine the response of students to the learning of mathematics.From the results of research that has been carried out, the conclusion to be drawn that the student response after follow the Learning Strategy with application Reciprocal Teaching using Microsoft Power Point is positive. Student learning outcomes in classical had reached complete by the percentage of 88%. It can be seen from the number of students who completed 22 of 25 students. Keywords: Strategies For Reciprocal Teaching, Microsoft Power Point, Student Response, Test Results Of The Study.